Taking the Leap: A Binational Translocation Effort to Close the 420-Km Gap in the Baja California Lineage of the California Red-Legged Frog (Rana draytonii) - North, Susan; Richmond, Jonathan Q.; Santana, Frank E.; Peralta-García, Anny; Gallegos, Elizabeth A.; Backlin, Adam R.; Hitchcock, Cynthia J.; Hollingsworth, Bradford D.; Valdez-Villavicencio, Jorge H.; Principe, Zachary; Fisher, Robert N.; Winchell, Clark S. (Frontiers in Conservation Science, 2022)
Conservation translocations, the human-mediated movement and release of a living organism for a conservation benefit, are increasingly recommended in species’ recovery plans as a technique for mitigating population declines or augmenting genetic diversity. However, translocation protocols for species with broad distributions may require regionally specific considerations to increase success, as environmental gradients may pose different constraints on population establishment and persistence in different parts of the range. Here we report on ongoing, genetically informed translocations of a threatened amphibian, California red-legged frog (Rana draytonii), from Baja California, México, to extirpated parts of the range in southern California in the United States, where contemporary stressors related to urbanization, invasive species, and aridification add to the natural environmental challenges already present for amphibians at this ‘warm edge’ of the range. We describe the collaborative binational planning required to jumpstart the effort, the fine-tuning of protocols for collection, transport, headstarting, and release of individuals, and results of multiple translocations, where time will tell whether the successes to date have reached their full potential. The steps outlined in this paper can serve as a template to inform future conservation translocations of imperiled amphibians across the U.S./México border, where the phylogenetics, historical biogeography and future habitat availability of a focal species are blind to political boundaries and critical to guiding recovery actions across the range.